Organizations and Strategies in Astronomy 7 - HECK, Andre (Astrophysics and Space Science Library, 2006)
This book is the seventh volume under the title Organizations and Strategies in Astronomy (OSA). The OSA series covers a large range of fields and themes: in practice, one could say that all aspects of astronomy-related life and environment are considered in the spirit of sharing specific expertise and lessons learned. The chapters of this book are dealing with socio-dynamical aspects of the astronomy (and related space sciences) community: characteristics of organizations, strategies for development, operational techniques, observing practicalities, journal and magazine profiles, public outreach, publication studies, relationships with the media, research communication, series of conferences, evaluation and selection procedures, research indicators, national specificities, contemporary history, and so on. The experts contributing to this volume have done their best to write in a way understandable to readers not necessarily hyperspecialized in astronomy while providing specific detailed information and sometimes enlightening 'lessons learned' sections. The book concludes with an updated bibliography of publications related to socio-astronomy and to the interactions of the astronomy community with the society at large. This volume will be most usefully read by researchers, editors, publishers, librarians, sociologists of science, research planners and strategists, project managers, public-relations officers, plus those in charge of astronomy-related organizations, as well as by students aiming at a career in astronomy or related space sciences.